Penerapan Simulasi Finite Element Terhadap Material Polylactic Acid Untuk Aplikasi Deker Kaki - Aulia Nanda, Rizki; Oktapian, Rizki; Taufik Ulhakim, Muhamad (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The Global Burden of Disease Report predicts that traffic accidents will rise from the 9th to the 3rd leading cause of death and disability by 2030. Motorized accidents pose a risk of knee impact during falls, which is a common hazard in various activities, particularly when riding a motorcycle. In some cases, personal protective equipment such as leg pads or decks are necessary. The utilization of PLA as a material for 3D printed footwear is an intriguing innovation. This research aims to manufacture a foot plug using 3D printing to practically determine the material's mechanical properties and simulate finite elements to achieve desired results, including lightweight (flexibility), customization, rapid prototyping, and ergonomic design integration. The ASTM D638 Type I specimen and foot plug were made of Polylactic Acid + Sunlu. The tensile test resulted in an average Tensile Strength (σ TS) of 28.03 Mpa, Displacement (u) of 4.98 mm, Elongation at break (δ) of 8.74%, and Modulus of Elasticity (E) of 0.319 Gpa. The finite element simulation showed that the maximum stress remained below the yield strength limit, with a safety factor of 2.03 in this research foot plug